1973
DOI: 10.3758/bf03198119
|View full text |Cite
|
Sign up to set email alerts
|

Remembering operations

Abstract: Two commonplace assumptions about encoding are that sentences are encoded and recognized on the basis of their semantic features primarily and that information regarding form features such as typography is typically ignored or discarded. These assumptions were tested in the present experiment where, within a signal-detection paradigm, S sorted sentences according to whether he had seen them before or not (old vs new) and, if they were old, whether their reappearance was in the same typography as on the first o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

25
177
4
1

Year Published

1983
1983
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 262 publications
(207 citation statements)
references
References 9 publications
25
177
4
1
Order By: Relevance
“…These results extend earlier findings of studies that had used less complex verbal material (Jacoby, 1978;Kolers, 1973;McDaniel, 1981). They also support the recent reformulations of levels of processing that focus on the elaborateness of processing and the resulting distinctiveness of the trace (Eysenck, 1979;Lockhart et al, 1976).…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…These results extend earlier findings of studies that had used less complex verbal material (Jacoby, 1978;Kolers, 1973;McDaniel, 1981). They also support the recent reformulations of levels of processing that focus on the elaborateness of processing and the resulting distinctiveness of the trace (Eysenck, 1979;Lockhart et al, 1976).…”
Section: Resultssupporting
confidence: 81%
“…They found that pairs for which one of the words had missing letters were remembered better than pairs for which both words were intact. More generally, the present result adds to a growing list of studies in which increasing the difficulty of processing an item has enhanced memory for that item (Kolers, 1973;Masson & Sala, 1978;McDaniel, 1981).…”
Section: Resultsmentioning
confidence: 65%
“…The results of the present study are consistent with several theoretical perspectives on memory (e.g., Anderson & Reder, 1979;Craik & Tulving, 1975;JohnsonLaird, Gibbs, & DeMowbray, 1978;Kolers, 1973Kolers, , 1975. For example, our results could have been predicted from Craik and Tulving's (1975) variant of the levels-of-processing perspective known as elaboration of processing.…”
Section: Discussionsupporting
confidence: 81%
“…It appears, then, that we unintentionally actively process items on a second occasion in much the same way as we processed them on the first occasion, even without any explicit requirement to do so. This is not surprising: It is in accord with the idea of transfer-appropriate processing (Morris et al, 1977), which meshes well with the proceduralist view of memory (Kolers, 1973;Kolers & Roediger, 1984). It is worth noting, however, that the benefit of transfer-appropriate processing stems from processing during encoding, whereas the benefit of source-constrained retrieval results from reprocessing of items during testing.…”
Section: Discussionsupporting
confidence: 55%